2014
DOI: 10.2322/tjsass.57.93
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transfer Alignment of Shipborne Gimbaled Inertial Navigation Systems

Abstract: Aiming at transfer alignment of gimbaled inertial navigation systems (INS) on a moving base, we propose an attitude matching alignment model to align the attitude of the slave platform. This method is achieved by applying an unscented Kalman filter to estimate the fixed misalignment angle, and the misalignment angle can be obtained only with attitude maneuvers, which are very easy for the ship to implement. Firstly, the frame dynamics equations are introduced. Then, frame angular error differential equations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…where K a0 is the accelerometer bias vector; K Ã a0x , K a1x , and K Ã a1x are diagonal matrices, whose components are the accelerometer bias asymmetries, scale factor errors, and scale factor asymmetries, respectively; t is the measurement noise vector. Equations (6)- (10) and (13) have shown that the dynamic model and the measurement model are both high nonlinearity. Besides, these equations indicate that the definition of the platform frame has a significant effect on the system model and the system observability.…”
Section: Isp's Self-ca System Modelsmentioning
confidence: 99%
“…where K a0 is the accelerometer bias vector; K Ã a0x , K a1x , and K Ã a1x are diagonal matrices, whose components are the accelerometer bias asymmetries, scale factor errors, and scale factor asymmetries, respectively; t is the measurement noise vector. Equations (6)- (10) and (13) have shown that the dynamic model and the measurement model are both high nonlinearity. Besides, these equations indicate that the definition of the platform frame has a significant effect on the system model and the system observability.…”
Section: Isp's Self-ca System Modelsmentioning
confidence: 99%
“…The floated inertial platform [1][2][3] is an advanced gimbal-free inertial platform using the hydrostatic supporting system instead of the gimbal system of the traditional inertial platform. 4,5 Generally, it is used as the navigation system of the long-range unmanned vehicle, such as the MX missile. 6 The structure and operating principle of the floated inertial platform have been detailed in Bai et al 7 The floated inertial platform is mainly composed of the sphere, shell and fluid filling the space between the sphere and shell, as shown in Figure 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…Various methods for in-flight coarse alignment have been researched recently. The conventional methods use an appropriate Kalman filter to estimate the initial attitude based on a linearized error model [5][6][7] or non-linear model [8][9][10] with large heading uncertainty. Contrary to the rapid response requirements, these methods require much time to converge to a stable value.…”
Section: Introductionmentioning
confidence: 99%